Alterations of EEG functional connectivity in resting state obese and overweight patients with binge eating disorder: A preliminary report. (21st October 2015) - Imperatori, Claudio; Fabbricatore, Mariantonietta; Farina, Benedetto; Innamorati, Marco; Quintiliani, Maria Isabella; Lamis, Dorian A.; Contardi, Anna; Della Marca, Giacomo; Speranza, Anna Maria
Highlights: Altered EEG resting state functional connectivity was observed in patients with BED. BED is related with increased EEG beta connectivity in frontal and visual areas. EEG connectivity values were significantly related to binge eating symptomatology. This pattern may reflect an hyper-excitability of the frontal and visual networks. Abstract: Alterations in brain functional connectivity have been detected in patients with eating disorders, but have not been studied in binge eating disorder (BED). We have investigated electroencephalographic (EEG) functional connectivity in thirteen overweight and obese patients with BED and thirteen overweight and obese patients without BED during RS condition. EEG analyzes were conducted by means of the exact Low Resolution Electric Tomography software (eLORETA). Compared to patients without BED, patients with BED demonstrated an increase of lagged phase synchronization in the beta frequency band among the cortical areas explored by FC1-T3 (left superior frontal gyrus—left middle temporal gyrus), T5-O1 (left inferior temporal gyrus—left middle occipital gyrus), and C4-O1 (right postcentral gyrus—left middle occipital gyrus) electrodes ( T = 4.861, p < 0.05). EEG connectivity values were also significantly related to binge eating symptomatology after controlling for depressive symptoms. Our results may reflect the impairment of frontal control network and visual processing networks, which lead patients with BED to be more vulnerable to food cues and lack of control with regards to over eating.